2017
DOI: 10.3390/s17091937
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Brain-Computer Interface for Decoding Motor Imagery Tasks within the Same Hand Using Choi-Williams Time-Frequency Distribution

Abstract: This paper presents an EEG-based brain-computer interface system for classifying eleven motor imagery (MI) tasks within the same hand. The proposed system utilizes the Choi-Williams time-frequency distribution (CWD) to construct a time-frequency representation (TFR) of the EEG signals. The constructed TFR is used to extract five categories of time-frequency features (TFFs). The TFFs are processed using a hierarchical classification model to identify the MI task encapsulated within the EEG signals. To evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 66 publications
0
49
0
Order By: Relevance
“…The EEG modality, which records the electrical potentials produced at different locations in the brain in response to an exogenous pain stimulus, is considered the most commonly used modality for designing objective pain detection systems. This can be attributed to several properties that are associated with the EEG modality, including the high temporal resolution, low-cost, and noninvasive nature [5,6]. Nonetheless, pain detection based on EEG signals analysis is considered challenging due to the nonstationarity nature of the EEG signals, low spatial resolution, and low signal-to-noise (SNR) ratio [7].…”
Section: Introductionmentioning
confidence: 99%
“…The EEG modality, which records the electrical potentials produced at different locations in the brain in response to an exogenous pain stimulus, is considered the most commonly used modality for designing objective pain detection systems. This can be attributed to several properties that are associated with the EEG modality, including the high temporal resolution, low-cost, and noninvasive nature [5,6]. Nonetheless, pain detection based on EEG signals analysis is considered challenging due to the nonstationarity nature of the EEG signals, low spatial resolution, and low signal-to-noise (SNR) ratio [7].…”
Section: Introductionmentioning
confidence: 99%
“…Classification results of rough sets method indicated that universal parameters couldn't be decided upon, and each subject had to be considered differently for parameter selection and classification. [1] For subject dependent training procedures, accuracy obtained in [3] is 88.8% for intact participants and 90.2% for amputated participants, and for subject independent training the accuracy was 80.8% and 87.8% respectively. Detecting actual motor activity of both hands with 80% accuracy and imaginary motor activity with just 34% accuracy in [7].…”
Section: Introductionmentioning
confidence: 99%
“…while EEG signals were recorded in 64 channel BCI2000 systems. [1] Eighteen intact and four amputated participants volunteered to perform and/or imagine to perform eleven motor imagery tasks with a single hand in [3] like finger and wrist movements, grasping tasks, etc. Eleven subjects participated for three hand and wrist movements MI experimenthand opening/ closing, wrist flexion/ extension and forearm pronation/ supination in [4] while EEG data was acquired using G.Nautilus headset with 16 electrodes positioned as per 10/20 system [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations